2018
DOI: 10.5702/massspectrometry.a0064
|View full text |Cite
|
Sign up to set email alerts
|

pH Dependence of the Number of Discrete Conformers of Carbonic Anhydrase 2, as Evaluated from Collision Cross-Section Using Ion Mobility Coupled with Electrospray Ionization

Abstract: Ion mobility experiments coupled with electrospray ionization (ESI) were conducted to evaluate the folding states of bovine carbonic anhydrase 2 (CA2) under three different pH conditions. Collision cross-section (CCS) of the CA2 ions generated by ESI revealed the presence of six discrete conformers in the gas phase under the conditions employed in this study. The CCS of the most extended conformer was three times larger than that of the most compact one. The charge state distribution of the CA2 ions was indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…The single bands observed at 43 V predominantly indicate a unimodal conformational distribution of BCA ions. The average CCS range from 2500 to 2625 Å 2 and slightly increase with protein charge, consistent with reported CCS values of native BCA 8,56,57 . This substantiates that post‐TIMS‐separation energetics do not alter the ion mobility profile.…”
Section: Resultssupporting
confidence: 87%
“…The single bands observed at 43 V predominantly indicate a unimodal conformational distribution of BCA ions. The average CCS range from 2500 to 2625 Å 2 and slightly increase with protein charge, consistent with reported CCS values of native BCA 8,56,57 . This substantiates that post‐TIMS‐separation energetics do not alter the ion mobility profile.…”
Section: Resultssupporting
confidence: 87%
“…A bimodal distribution appears in the denatured mass spectra that suggest an expanded, flexible structure, potentially with multiple conformers. Nabuchi et al 65 noted that at pH 3.8 the mass spectrum of carbonic anhydrase shows a bimodal distribution, comprised of the apoprotein with a CSD of 11+ to 38+ and the holo (zincbound)-protein with a CSD of 10+ to 20+. In a follow-up study, 66 these researchers demonstrated that a drop in pH from 5.0 to 3.6 resulted in the loss of Zn 2+ and in significant unfolding of the N-terminus.…”
Section: ■ Results and Discussionmentioning
confidence: 99%